The effect of aerobic training with silymarin consumption on some cardiovascular risk factors in men with type 2 diabetes - Eraj Baghery Nasab Najaf Abad; Ali Khajehlandi; Amin mohammadi (Jorjani Biomedicine Journal, 2020)
Background and objective: Type 2 diabetes (T2D) is a metabolic disease that leads to increased levels of lipids, therefore the present study aimed to investigate the effect of eight weeks of aerobic training(AT) with silymarin (S)consumption on lipid profile in men with type 2 diabetes. Methods: 60 middle-aged male volunteers were randomly divided into 4 groups, including: (1) control(C) + placebo, (2) AT + placebo, (3) S consumption and (4) AT+S consumption. The AT groups performed for eight weeks, three sessions per week and 20-45 minutes per session at an intensity of 60 to 85% of the reserve heart rate, and the S groups of consumed 140 mg / kg of S daily (in two meals).  Serum levels of Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL), Cholesterol (CHO), and Triglyceride (TG) were measured before and after the test. Data were analyzed using one-way ANOVA and Bonferroni’s test, and P value less than 0.05 was considered significant. Results: AT reduced serum levels of LDL, CHO, TG and increased HDL in men with T2D(P ≥ 0.05). Consumption of S reduced LDL, CHO, TG and increased HDL in men with T2D(P ≥ 0.05). AT and S consumption reduced LDL, CHO, TG and increased HDL; also, decrease in LDL, CHO, TG and increase in HDL in the AT and S consumption group was more favorable than the effect of S alone (P ≥ 0.05). Conclusion: It seems that AT and S consumption simultaneously have interactive effects on reducing LDL, CHO, TG and increasing HDL in men with T2D.